Formulasi sediaan lotion ekstrak daun nangka (Artocarpus Heterophyllus) sebagai repelan terhadap nyamuk aedes aegypti - Marcellia, Selvi; Nofita, Nofita; Triyanti, Yesicha (JOURNAL OF Pharmacy and Tropical Issues, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by a virus that is transmitted through the bite of the Aedes aegypti mosquito which has been infected by the dengue virus from DHF patients. Jackfruit leaf extract containing saponins, flavonoids, alkaloids, terpenoids, steroids and tannins can kill the Aedes aegypti mosquito. Based on the background of the researchers interested in testing the formulation of the Jackfruit Leaf Extract Lotion (Artocarpus heterophyllus) as a repellent against the Aedes aegypti mosquito. Purpose: To determine the effect of repellant extract of jackfruit leaf (Artocarpus heterophyllus) against Aedes aegypti mosquitoes. Method: Extraction of percolation with various tests, including the test of alkaloids, flavonoids, saponins, tannins, steroids, triterpenoid, evaluation of mosquito repellent lotions. Results: The concentration of jackfruit leaf extract (Artocarpus heterophyllus) in lotion preparations was the most effective as a mosquito repellant Aedes aegypti, namely at a concentration of 9% with almost the same effectiveness as the positive control, namely 86% at 30 seconds and per 6 hours got an average of 79 .5% with a statistical test value of p < 0.05. Conclusion: Jackfruit leaf extract in lotion preparation has effectiveness in repelling mosquitoes. Keywords: Dengue Fever; Jackfruit leaves (Artocarpus heterophyllus); Aedes aegypti mosquito Pendahuluan: Demam Berdarah Dengue (DBD) merupakan penyakit yang disebabkan oleh virus yang ditularkan melalui gigitan nyamuk Aedes aegypti yang sebelumnya telah terinfeksi oleh virus dengue dari penderita DBD. Ekstrak daun nangka yang mengandung saponin, flavonoid, alkaloid, terpenoid, steroid dan tanin dapat membunuh nyamuk Aedes aegypti. Berdasarkan latar belakang peneliti tertarik untuk melakukan Uji Formulasi Sediaan Lotion Ekstrak Daun Nangka (Artocarpus heterophyllus) sebagai Repelan Terhadap Nyamuk Aedes aegypti. Tujuan: Untuk mengetahui efek Repelan ekstrak daun nangka (Artocarpus heterophyllus) terhadap nyamuk Aedes aegypti. Metode: Ekstraksi perkolasi dengan berbagai uji diantaranya uji alkaloid, flavonoid, saponin, tanin, steroid, triterpenoid, evaluasi lotion anti nyamuk. Hasil: Konsentrasi ekstrak daun nangka (Artocarpus heterophyllus) dalam sediaan lotion yang paling efektif sebagai reppelan nyamuk Aedes aegypti yaitu pada konsentrasi 9% dengan daya efektivitas yang hampir sama dengan kontrol positif yaitu 86% pada 30 detik dan per 6 jam diperoleh rata-rata 79,5% dengan nilai uji statistik p < 0,05. Simpulan: Ekstrak daun nangka dalam sediaan lotion memiliki efektivitas dalam menolak nyamuk.Kata kunci: Demam Berdarah; Daun Nangka (Artocarpus heterophyllus); Nyamuk Aedes aegypti. Kata Kunci: Demam Berdarah; Daun nangka (Artocarpus heterophyllus); Nyamuk Aedes aegypti